The Parameters Calibration of Additive Mass Method and Its Application in Compaction Density Measurement of Soil Rock Mixtures - Zhiyu Dai; Zili Wang; Yongsheng Li; Jiehao Xu (Advances in Civil Engineering)
The additive mass method (AMM) is applied to test the compaction density of soil–rock mixtures (S–RMs) due to its high efficiency, nondestructiveness and accuracy. However, there is no systematic research on influence factor of AMM. In this study, AMM test parameters were systematically calibrated first, and a calculation model for the compaction density of S–RM was established in the test area. After that, the AMM was applied in the on-site detection of the compaction density of an earth–rockfill dam. After calibration test, the main geophone frequency was 40 Hz, the drop distance and offset distance were 20 and 70 cm, respectively, and set the ∆m of five levels as 38, 88, 138, 213, and 288 kg. The detection error of K–K/ρ model had a better precision than the ω−2−ω−2/ρ model through on-site testing and verification. A new calculation model with lower accuracy based on vibration stiffness–vibration stiffness/density K−K/ρ) model was proposed according to the test error distribution. It was found that the test error of the K−K/ρ model was reduced to 0.9%. The results demonstrated that the AMM could accurately detect the compaction density of S–RM after the test parameters were reasonably determined.